Economic development and climate change: Achieving a sustainable balance - Ana Glavina; Katarina Mišić; Jakov Baleta; Jin Wang; Hrvoje Mikulčić (Cleaner Engineering and Technology)
This review analyzes the effects of economic growth and technological progress on the environment, exploring how modern technology and human behaviors are adapted to minimize environmental impact and promote sustainable development. It examines the role of economic networks and input-output models in understanding intersectoral connections and trade flows, particularly in the context of climate change mitigation and adaptation. Special emphasis is placed on carbon sequestration technologies and carbon accounting methodologies, which are essential for monitoring emissions, assessing carbon footprints, and formulating effective climate policies. Over the past decade, researchers have extensively studied the relationship between economic growth and climate change using various econometric methodologies. The Environmental Kuznets Curve hypothesis suggests that at a certain stage of development, further economic growth can lead to reduced pollution levels. Sector-specific approaches highlight potential solutions for climate change mitigation, emphasizing the need for synergy between technological innovations and human behavior. Carbon sequestration, carbon capture and utilization, and pro-environmental practices play pivotal roles in this transition. By integrating policy support, community engagement, and awareness programs, societies can foster a transformation towards a sustainable future, balancing economic growth with environmental responsibility. This review highlights the intricate relationships between economic systems, technological advancement, and environmental sustainability, offering insights into effective strategies for addressing climate challenges.